Women with celiac disease present with fertility problems no more often than women in the general population - Dhalwani, Nafeesa N.; West, Joe; Sultan, Alyshah Abdul; Ban, Lu; Tata, Laila J. (Elsevier, 2014)
BACKGROUND & AIMS: Studies have associated infertility with celiac disease. However, these included small numbers of women attending infertility specialist services and subsequently screened for celiac disease, and therefore may not have been representative of the general population. We performed a large population-based study of infertility and celiac disease in women from the United Kingdom.